Synthesis and Biological Activity Evaluation of New Imidazo and Bis Imidazo (1, 2-A) Pyridine Derivatives - Naeemah Al-Lami (Journal of Global Pharma Technology, 2018)
A series of imidazo [1, 2-a] pyridine derivatives were obtained from the work that was conducted in this research. Firstly; reaction of 2-amino pyridine with (4-phenyl phenacyl bromide) or (4-bromo phenyl phenacyl bromide) to give 2-substituted imidazo [1, 2-a] pyridine as a starting compound (1a, 1b).Then reactions of compounds (1a, 1b) were carried out through two pathways: the first pathway involved condensation of two analogous of compounds (1a, 1b) with different aryl aldehyde to give bis imidazo [1, 2-a] pyridine (2a, 3a, 4a, 2b, 3b, 4b). While; the second pathway was introduced Carbaldehyde group at position-3 of prepared 2-substituted imidazo pyridine rings by Vilsmeier-Haack reaction, the produced was reacted with different aromatic amines to give Schiff bases of these derivatives. Then Schiff bases reacted with α-amino acid, monochloro acetic acid and phenyl isocyanate to give compounds (10a-15b). The new prepared compounds were identified by [FTIR, 1H-NMR and 13C-NMR] and their physical properties were measured. Furthermore, we have evaluated the effect of some prepared compounds on some bacterial and fungal strains. Keywords: Imidazo/pyridine, Bis imidazo, Aza-β-lactam, oxazolidin, imidazolinone.